2022
DOI: 10.34150/jpak.v22i2.386
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kehidupan Rohani Umat Paroki Terhadap Minat Siswa Kota Ruteng Dalam Mendalami Kitab Suci

Abstract: This study aims to describe the influence of the parish spiritual life toward students' interest in studying the Bible. This study used a quantitative approach. The research sample consisted of 332 high school students, both private and public, in the city of Ruteng, Manggarai Regency, which were taken using a proportional random technique. The data collection instrument used a closed questionnaire. The data analysis technique used Pearson Product Moment Correlation with SPSS version 23.0. The results of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Dalam studi Kitab Suci khususnya terkait dengan hermeneutika biblis dikenal sejumlah metode penafsiran Kitab Suci, yaitu metode historis kritis, metode analisis literer, metode kanonis, dan metode praktis. Toron & Manca (2022) menjelaskan beberapa metode tersebut lebih lanjut. Pertama, Metode Historis Kritis.Dalam metode ini, penafsir berupaya untuk mempelajari Kitab suci dalam konteks historisnya sehingga bisa menemukan pesan yang mau disampaikan.…”
Section: Metode-metode Penafsiran Kitab Suciunclassified
“…Dalam studi Kitab Suci khususnya terkait dengan hermeneutika biblis dikenal sejumlah metode penafsiran Kitab Suci, yaitu metode historis kritis, metode analisis literer, metode kanonis, dan metode praktis. Toron & Manca (2022) menjelaskan beberapa metode tersebut lebih lanjut. Pertama, Metode Historis Kritis.Dalam metode ini, penafsir berupaya untuk mempelajari Kitab suci dalam konteks historisnya sehingga bisa menemukan pesan yang mau disampaikan.…”
Section: Metode-metode Penafsiran Kitab Suciunclassified
“…Therefore, researchers recommend intensifying the pastoral apostolate of the Holy Bible for young Catholics [8]. Toron et al's research found that parish spiritual activities influenced the growth of high school/vocational school students' interest in the Holy Bible [9]. Research with the same location and research subject was carried out by Oswaldus Bule, Marselus Ruben Payong, and Hendrikus Midun, but they highlighted the aspect of frequency of reading the Holy Bible and its influence on students' interest in the Holy Bible.…”
Section: Introductionmentioning
confidence: 99%